THE EFFECTIVENESS OF CREATIVE-PRODUCTIVE METHODS ORIENTED ON LOCAL WISDOM TOWARDS TEXT WRITING SKILLS OF STUDENTS IN CLASS VII SMP (KEEFEKTIFAN METODE KREATIF-PRODUKTIF BERORIENTASI KEARIFAN LOKAL TERHADAP KETERAMPILAN MENULIS TEKS SISWA KELAS VII SMP) - Rahayu Fitri; Rina Sartika; Yulia Pebriani; Ricci Gemarni Tatalia; Refa Lina Tiawati; Upit Yulianti (Universitas PGRI Sumatera Barat, 2022)
This research aims to describe the effectiveness of the creative-productive method oriented to local wisdom on the text-writing skills of seventh-grade students of SMP Negeri 38 Padang. The texts analyzed in this study are descriptive, fantasy stories, and procedures. The findings indicate that the texts written by students are not according to the structure and linguistic rules of the text that have been set. This type of research is quantitative research with experimental methods in the form of Pre-Experimental Design. The design in this research is the One-Group Pretest-Posttest Design. The sampling technique in this research is a simple random sampling technique. The sample in this research was class VII E about 32 students. Data collection was carried out in June 2021. Based on the results of data analysis, it can be concluded that the creative-productive method oriented to local wisdom is effectively used for learning to write descriptive texts, fantasy stories, and procedures for seventh-grade students of SMP Negeri 38 Padang. Based on the results of the comparison of the value of the hypothesis test, the creative-productive method oriented to local wisdom is most effectively applied to description texts, compared to fantasy story texts and procedural texts.